Processing aid, thermoplastic resin composition, film, and method for producing same

By using low moisture content ethylene-acetic acid copolymer as treatment aid and adjusting its melting flow rate and ethylene content, the problem of resin melting phenomenon during high-speed meltblowing is solved, and the surface improvement and production efficiency of the finished resin product are achieved.

JP7653046B2Active Publication Date: 2025-03-28DAIKIN INDUSTRIES LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024076662
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2024-01-05
Filing Date
2024-05-09
Publication Date
2025-03-28
Estimated Expiration
2044-05-09

AI Technical Summary

Technical Problem

During the high-speed meltblowing process, the melt-treated thermoplastic resin composition is prone to melting, resulting in rough surfaces and unable to obtain good finished products.

Method used

Treatment aids containing low moisture content of ethylene-acetic acid copolymers are used, and their melt flow rate and ethylene content are adjusted within a specific range to improve the flowability and pressure stability of the resin.

Benefits of technology

It effectively improves the surface quality of the finished product of the resin, improves the mechanical properties and production efficiency of the finished product, and maintains good pressure stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653046000001
    Figure 0007653046000001
  • Figure 0007653046000002
    Figure 0007653046000002
  • Figure 0007653046000003
    Figure 0007653046000003
Patent Text Reader

Abstract

To provide a processing aid which is capable of improving the processability of a thermoplastic resin; and a thermoplastic resin composition and a film, each using this processing aid.SOLUTION: The present disclosure provides a processing aid which contains an ethylene-vinyl alcohol copolymer and has a moisture content of 0.3 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present disclosure relates to processing aids, thermoplastic resin compositions and films, and methods for making the same. [Background technology]

[0002] In the processing of melt-processable thermoplastic resins, high-speed extrusion is necessary to improve productivity and reduce costs. However, melt-processable thermoplastic resin compositions always have a critical shear rate, and if this rate is exceeded, a condition called melt fracture occurs, resulting in a rough surface, making it impossible to obtain good molded products.

[0003] As a method for improving the processability of thermoplastic resins, for example, Patent Document 1 proposes a method of using a predetermined amount of ethylene-vinyl alcohol copolymer, but the effect is not sufficient. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 1-215840 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present disclosure is to provide a processing aid that can improve the processability of thermoplastic resins, a thermoplastic resin composition and film using the same, and methods for producing the same. [Means for solving the problem]

[0006] The present disclosure (1) is a processing aid that contains an ethylene-vinyl alcohol copolymer and has a moisture content of 0.3% by mass or less.

[0007] The present disclosure (2) is the processing aid according to the present disclosure (1), wherein the ethylene-vinyl alcohol copolymer has a melt flow rate of 40 g / 10 min or less at 190° C. under a load of 2.16 kgf.

[0008] The present disclosure (3) is the processing aid according to the present disclosure (1) or (2), wherein the ethylene-vinyl alcohol copolymer has an ethylene content of 5 to 50 mol %.

[0009] The present disclosure (4) is the processing aid according to any one of the present disclosures (1) to (3), wherein the ethylene-vinyl alcohol copolymer has a melt flow rate of 1.5 g / 10 min or more and 50 g / 10 min or less at 190°C and a load of 2.16 kgf, and the ethylene-vinyl alcohol copolymer has an ethylene content of 32 to 48 mol%.

[0010] The present disclosure (5) is the processing aid according to any one of the present disclosures (1) to (4), which is a masterbatch further containing a thermoplastic resin (A).

[0011] The present disclosure (6) is the processing aid according to the present disclosure (5), wherein the thermoplastic resin (A) is a polyolefin resin.

[0012] The present disclosure (7) is the processing aid according to the present disclosure (6), wherein the polyolefin resin is polyethylene.

[0013] The present disclosure (8) is the processing aid according to any one of the present disclosures (5) to (7), wherein the mass ratio of the thermoplastic resin (A) to the ethylene-vinyl alcohol copolymer (thermoplastic resin (A):ethylene-vinyl alcohol copolymer) is 99:1 to 40:60.

[0014] The present disclosure (9) is the processing aid according to any one of the present disclosures (5) to (8), wherein the thermoplastic resin (A) is at least one selected from the group consisting of low-density polyethylene, metallocene-catalyzed linear low-density polyethylene, and Ziegler-Natta-catalyzed linear low-density polyethylene, and the mass ratio of the thermoplastic resin (A) to the ethylene-vinyl alcohol copolymer (thermoplastic resin (A):ethylene-vinyl alcohol copolymer) is 93:7 to 25:75.

[0015] The present disclosure (10) is the processing aid according to any one of the present disclosures (1) to (9), which is substantially free of fluorine.

[0016] The present disclosure (11) is the processing aid according to any one of the present disclosures (5) to (9), which has a melt flow rate of 0.01 to 100 g / 10 min at 190° C. under a load of 2.16 kgf.

[0017] The present disclosure (12) is a thermoplastic resin composition containing the processing aid according to any one of the present disclosures (1) to (11) and a thermoplastic resin (B).

[0018] The present disclosure (13) is the thermoplastic resin composition according to the present disclosure (12), wherein the thermoplastic resin (B) is a polyolefin resin.

[0019] The present disclosure (14) is the thermoplastic resin composition according to the present disclosure (13), wherein the polyolefin resin is polyethylene.

[0020] The present disclosure (15) is the thermoplastic resin composition according to any one of the present disclosures (12) to (14), wherein the content of the ethylene-vinyl alcohol copolymer is 0.001 to 2 mass %.

[0021] The present disclosure (16) is the thermoplastic resin composition according to any one of the present disclosures (12) to (15), wherein the thermoplastic resin (B) is at least one selected from the group consisting of metallocene-catalyzed linear low-density polyethylene and Ziegler-Natta-catalyzed linear low-density polyethylene, and the content of the ethylene-vinyl alcohol copolymer is 0.04 to 0.2 mass%.

[0022] The present disclosure (17) is a film using the thermoplastic resin composition according to any one of the present disclosures (12) to (16).

[0023] The present disclosure (18) is a method for producing the processing aid according to any one of the present disclosures (1) to (11), including a mixing step and a discharging step.

[0024] The present disclosure (19) is a method for producing the thermoplastic resin composition according to any one of the present disclosures (12) to (16), including a mixing step and a discharging step.

[0025] The present disclosure (20) is a method for producing the film according to the present disclosure (17), which includes a molding step. [Effects of the Invention]

[0026] According to the present disclosure, the processability of thermoplastic resins can be improved. DETAILED DESCRIPTION OF THE INVENTION

[0027] The present disclosure will be specifically described below.

[0028] <Processing aids> The processing aid of the present disclosure contains an ethylene-vinyl alcohol copolymer (EVOH) and has a moisture content of 0.3% by mass or less.

[0029] As shown in the examples described later, when an ethylene-vinyl alcohol copolymer is added during processing of a thermoplastic resin, the melt fracture state is improved compared to when an ethylene-vinyl alcohol copolymer is not added, but pressure stability tends to decrease. In contrast, the processing aid of the present disclosure can improve pressure stability to a good level while improving melt fracture.

[0030] The melt flow rate (MFR) of the ethylene-vinyl alcohol copolymer is preferably 0.001 g / 10 min or more, more preferably 0.1 g / 10 min or more, even more preferably 0.5 g / 10 min or more, still more preferably 1.5 g / 10 min or more, and is preferably 50 g / 10 min or less, more preferably 40 g / 10 min or less, even more preferably 20 g / 10 min or less, still more preferably 10 g / 10 min or less. If it is within the above range, the effect of improving processability will be better. In this specification, MFR is measured in accordance with ASTM D 1238 under conditions of 190°C and a load of 2.16 kgf.

[0031] The ethylene content of the ethylene-vinyl alcohol copolymer is preferably 5 mol% or more, more preferably 10 mol% or more, even more preferably 15 mol% or more, still more preferably 32 mol% or more, and is preferably 50 mol% or less, more preferably 48 mol% or less, still more preferably 40 mol% or less. Within the above ranges, the effect of improving processability is more excellent. In this specification, the ethylene content is determined by nuclear magnetic resonance (NMR) method.

[0032] The ethylene-vinyl alcohol copolymer is preferably one obtained by saponifying an ethylene-vinyl ester copolymer, and among these, one obtained by saponifying an ethylene-vinyl acetate copolymer is particularly preferred.

[0033] The saponification degree of the ethylene-vinyl alcohol copolymer is preferably 80 to 100 mol %.

[0034] When copolymerizing ethylene and vinyl acetate, other fatty acid vinyl esters (such as vinyl propionate and vinyl pivalate) can also be used in combination. Furthermore, the ethylene-vinyl alcohol copolymer can contain 0.0002 to 0.2 mol% of a vinylsilane compound as a copolymerization component. Examples of vinylsilane compounds include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, and γ-methacryloxypropylmethoxysilane. Among these, vinyltrimethoxysilane and vinyltriethoxysilane are preferred.

[0035] When copolymerizing ethylene and vinyl acetate, it is also possible to coexist in small amounts with monomers other than the above-mentioned fatty acid vinyl esters and vinylsilane compounds, such as α-olefins such as propylene, isobutylene, α-octene, and α-dodecene; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, and itaconic acid, or their anhydrides, salts, or mono- or dialkyl esters; nitriles such as acrylonitrile and methacrylonitrile; amides such as acrylamide and methacrylamide; olefin sulfonic acids such as ethylene sulfonic acid, allyl sulfonic acid, and methallylsulfonic acid, or their salts; alkyl vinyl ethers, vinyl ketone, N-vinylpyrrolidone, vinyl chloride, and vinylidene chloride.

[0036] In the ethylene-vinyl alcohol copolymer, the content of polymerized units based on monomers other than ethylene and vinyl alcohol is preferably 10 mol % or less, more preferably 5 mol % or less, and even more preferably 1 mol % or less. The lower limit is not particularly limited, and may be 0 mass %. In this specification, the content of polymerized units based on monomers other than ethylene and vinyl alcohol is determined by nuclear magnetic resonance (NMR) spectroscopy.

[0037] In the processing aid of the present disclosure, the content of the ethylene-vinyl alcohol copolymer is preferably 40% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. The upper limit is not particularly limited, and may be 100% by mass. In the processing aid of the present disclosure, the content of the ethylene-vinyl alcohol copolymer may be 70% by mass or more, 80% by mass or more, or 90% by mass or more. The upper limit is not particularly limited, and may be 100% by mass.

[0038] The processing aid of the present disclosure preferably contains a synergist that is at least one selected from the group consisting of a polyol having a melting point of 80°C or less, polycaprolactone, silicone, and a polyamide-polyether block copolymer. This improves processability. Furthermore, the above-mentioned polyols are preferred as synergists because of their excellent processability improvement effect.

[0039] The melting point of the polyol may be 80° C. or lower, preferably 75° C. or lower, more preferably 70° C. or lower, and even more preferably 68° C. or lower, and is preferably 10° C. or higher, more preferably 20° C. or higher, and even more preferably 25° C. or higher. Within the above ranges, the effect of improving processability is better.

[0040] The polyol may be, for example, A[(OR 11 ) x2 OR 12 ] y2 wherein A is typically an alkylene having one or more ether bonds, y2 is 2 or 3, and (OR 11 ) x2 is an oxyalkylene group, OR 11 is a poly(oxyalkylene) chain having multiple (x2) R 11 are each independently C2-C5 alkylene, and in some embodiments, C2-C3 alkylene; R 12is hydrogen, alkyl, aryl, arylalkenyl, alkylarylenyl, —C(O)-alkyl, —C(O)-aryl, —C(O)-arylalkenyl or —C(O)-alkylarylenyl, and —C(O)— is OR 12 It is bonded to O. x2 is 10 to 230,000.

[0041] The polyol is R 11 a homopolymer of poly(oxyethylene) in which R is -CH2CH2-, or 11 is —C3H6—, and the like.

[0042] The polyols may be chains of randomly distributed oxyalkylene groups (e.g., copolymers of -OC2H4- and -OC3H6- units) or alternating blocks of repeating oxyalkylene groups (e.g., (-OC2H4-) a1 Block and (-OC3H6-) b1 It may also be a chain having a polymer containing blocks, where a1+b1 is 10 to 230,000.

[0043] In some embodiments of the above polyols, A is ethylene, —CH—CH(—)—CH— (derived from glycerol), CHCHC(CH—) (derived from 1,1,1-trimethylolpropane), poly(oxypropylene), —CHCH—O—CHCH—, or —CHCH—O—CHCH—O—CHCH—; and R 2 is hydrogen, methyl, butyl, phenyl, benzyl, acetyl, benzoyl or stearyl.

[0044] The polyol is a dicarboxylic acid and A[(OR 11 ) x2 OR 12 ] y2 A polyester prepared from a poly(oxyalkylene) polymer represented by the formula: 11 and x2 are as defined above, and R 12is hydrogen and y2 is 2.

[0045] The polyols may be used alone or in combination of two or more. From the viewpoint of excellent effect of improving processability, polyethylene glycol and polyethylene oxide are preferred, and polyethylene glycol is particularly preferred.

[0046] The number average molecular weight (Mn) of the polyethylene glycol is preferably 1,000 or more, more preferably 3,000 or more, and even more preferably 5,000 or more, and is preferably 50,000 or less, more preferably 45,000 or less, and even more preferably 40,000 or less. Within the above ranges, the effect of improving processability is better. In this specification, the number average molecular weight is calculated from the hydroxyl value measured in accordance with JIS K0070.

[0047] The viscosity average molecular weight (Mv) of the polyethylene oxide is preferably 100,000 or more, more preferably 120,000 or more, even more preferably 140,000 or more, and is preferably 10,000,000 or less, more preferably 1,600,000 or less, even more preferably 500,000 or less. Within the above ranges, the effect of improving processability is better. In this specification, the viscosity average molecular weight is calculated as follows. Using an Ostwald viscometer, the specific viscosity ηsp of aqueous solutions of various polymer concentrations c (g / dl) in pure water is measured at 35°C, and [η] is calculated by dividing the specific viscosity by the polymer concentration to obtain a reduced viscosity (ηsp / c) based on the relationship between the polymer concentration c and the polymer concentration c, by extrapolating the polymer concentration c to 0. [η] is inserted into the following equation to calculate the viscosity-average molecular weight M. Formula: [η] = 6.4 × 10 -5 M 0.82

[0048] The polycaprolactone may be a homopolymer of ε-caprolactone or a modified polycaprolactone, such as one modified by ring-opening polymerization of ε-caprolactone in the presence of 1,4-butanediol or the like, or one modified at the end of the polymer with an ether or ester group or the like.

[0049] The weight-average molecular weight (Mw) of the polycaprolactone is preferably 2,000 or more, more preferably 10,000 or more, and even more preferably 25,000 or more, and is preferably 100,000 or less, more preferably 95,000 or less, and even more preferably 90,000 or less. Within the above ranges, the effect of improving processability is better. In this specification, the weight average molecular weight is measured by gel permeation chromatography (GPC) in terms of polystyrene.

[0050] The melting point of the polycaprolactone is preferably 80° C. or lower, more preferably 75° C. or lower, even more preferably 70° C. or lower, still more preferably 68° C. or lower, and is preferably 10° C. or higher, more preferably 20° C. or higher, and even more preferably 45° C. or higher. Within the above ranges, the effect of improving processability is more favorable.

[0051] Said silicone can in principle be all organosilicon compounds known to those skilled in the art under the term silicone polymer.A suitable definition of silicone can be found in Winnacker / Kuchler: "Chemische Technik" [Chemical Technology], R.Dittmeyer, W.Keim, G.Kreysa, A.Oberholz (editors), Volume 5: "Organische Zwischenverbindungen, Polymere" [Organic Intermediates, Polymers], Chapter: "Silicones", Wiley-VCH, Weinheim, 2005.

[0052] Silicone can be substituted or unsubstituted linear oligo- or polydiorganosiloxane, branched silicone polymer, silicone resin or crosslinked silicone polymer.Of course, mixtures of various silicone polymers can also be used.As mentioned above, silicone-containing copolymers can also be used, such as polyether functional silicone, silicone containing urea or urethane unit, or silicone block copolymers with organic polymers.For the purpose of better compatibility, it is particularly preferred to use high molecular weight polydiorganosiloxanes, which can also contain non-silicone components, such as fillers such as finely divided silica, chalk, talc and sheet silicate.

[0053] Preferably, the silicone polymer corresponds to formula A, where R 13 3SiO 1 / 2 ] a2 [SiR 13 2O 2 / 2 ] b2 [R 13 SiO 3 / 2 ] c2 [SiO 4 / 2 ] d2 , where R 13 is hydrogen, -OH, or an unsubstituted or substituted C1 to C18 hydrocarbon residue, a2, b2, c2, and d2 each represent 0 or an integer, and a2+b2+c2+d2 is an integer from 5 to 10,000.

[0054] C1 to C18 hydrocarbon residues R 13Examples of alkyl residues are alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, 2-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, hexyl groups such as n-hexyl, heptyl groups such as n-heptyl, octyl groups such as n-octyl and isooctyl, nonyl groups such as n-nonyl, decyl groups such as n-decyl, cycloalkyl groups such as cyclopentyl, cyclohexyl, 4-ethylcyclohexyl and cycloheptyl, norbornyl and methylcyclohexyl. Among alkyl groups, C1 to C6 groups are preferred, such as methyl and ethyl groups, especially methyl.

[0055] R 13 Examples of unsaturated C1 to C18 hydrocarbon residues include alkenyl residues such as vinyl, 2-propen-2-yl, allyl, 3-buten-1-yl, 5-hexen-1-yl, 10-undecen-1-yl, and cycloalkenyl residues (2-cyclohexenyl, 3-cyclohexenyl, cyclopentadienyl, 2-(cyclohex-3-en-1-yl)ethyl); aryl residues such as phenyl, biphenylyl, and naphthyl; alkaryl residues such as o-, m-, and p-tolyl and phenethyl residues (2-phenylethyl, 1-phenylethyl), and aralkyl residues such as benzyl. Preferred unsaturated C1 to C18 hydrocarbon residues R 13 are vinyl and phenyl residues.

[0056] residue R 13 Examples of substituted hydrocarbon residues as are halogenated hydrocarbons, such as the chloromethyl, 3-chloropropyl, 3-bromopropyl, 3,3,3-trifluoropropyl and 5,5,5,4,4,3,3-heptafluoropentyl residues, as well as the chlorophenyl, dichlorophenyl and trifluorotolyl residues.

[0057] residue R 13 is preferably bonded to the silicone polymer of formula A via an Si-C bond, but can also be bonded to the silicone polymer via an oxygen atom -O-.

[0058] R 13 preferably has 1 to 6 carbon atoms. The ethyl, phenyl, vinyl and methyl residues are particularly preferred.

[0059] Preferably, a2+b2+c2+d2 means a number of at least 10, particularly preferably at least 100, in particular at least 1000 and at most 15000, particularly preferably at most 10000, in particular at most 7000.

[0060] Preferably, c2+d2 means <0.1*(a2+b2+c2+d2), in particular c2+d2<0.05*(a2+b2+c2+d2).

[0061] Preferably, all residues R 13 At least 50%, particularly preferably at least 70%, in particular at least 80% of these represent methyl residues.

[0062] In principle, all silicone polymers corresponding to formula A can be used. However, preference is given to silicone polymers having a dynamic viscosity of more than 1000 mPa.s, preferably measured according to DIN EN ISO 3219:1994 and DIN 53019 using an Anton Paar "MCR 302" rheometer with a 2° opening angle, a 50 mm diameter plate-cone system (cone CP50-2), a measuring temperature of 25.00°C ± 0.05°C, and a shear rate of 1 sec-1.

[0063] Among silicones, silicone polymers having very high molecular weights, such as UHMW polysiloxanes (ultra-high molecular weight; described in KJ Ryan et al., Journal of Vinyl & Additive Technology, March 2000, Vol. 6, No. 1, pp. 7-19), may be used.

[0064] The degree of polymerization of UHMW polysiloxanes ranges from >1000 to about 14000, which corresponds to a number average molecular weight between 74 kg / mol and 1000 kg / mol.

[0065] Typical UHMW polysiloxanes have a dynamic viscosity of between 10 kPa·s and 50 kPa·s, preferably between 15 kPa·s and 30 kPa·s, measured with an airborne rotational rheometer according to DIN EN ISO 3219:1994 and DIN 53019, using a plate-plate system (25 mm diameter) with a measuring gap of 0.5 mm. The measurement temperature is 25.00°C + / - 0.1°C. The shear rate gradient is 0.1 sec -1 The viscosity reported represents the arithmetic mean of three individual measurements carried out independently.

[0066] Of the above UHMW polysiloxanes, high molecular weight polydimethylsiloxanes having a dynamic viscosity (preferably measured by the method described above) between 1 kPa·s and 50 kPa·s, preferably between 10 and 40 kPa·s, and particularly preferably between 15 and 30 kPa·s, are particularly preferred, as they are inexpensive and effective.

[0067] Examples of the UHMW polysiloxane include commercially available UHMW polysiloxanes such as MULTIBASE (registered trademark) MB50-001 and MULTIBASE (registered trademark) MB50-002 manufactured by DuPont, and GENIOPLAST (registered trademark) PELLET S, GENIOPLAST (registered trademark) PELLET P Plus, GENIOPLAST (registered trademark) PE50S08, and GENIOPLAST (registered trademark) PP50S12 manufactured by Wacker Asahi Kasei Silicones, and mixtures thereof, with MB50-002 and GENIOPLAST (registered trademark) PELLET S being preferred.

[0068] Silicone polymers are commercially available as ready-to-use pellets / granules or masterbatches, which can be mixed into thermoplastic granules, for example, prior to their further processing.

[0069] The polyamide-polyether block copolymer is a copolymer having a polyamide block and a polyether block in the polymer backbone. In the present disclosure, such a block copolymer having a polyamide block and a polyether block may also be referred to as a "polyamide / polyether block copolymer." It may also be abbreviated as a "PEBA copolymer" or "PEBA." In some embodiments of the present disclosure, the PEBA copolymer can be represented by the following general formula: [ka]

[0070] Here, PA is the polyamide block, PE is the polyether block, and p is the length of the PEBA copolymer, which represents the total number of polyamide and polyether blocks. In some embodiments of the present disclosure, the PEBA copolymer can be represented by the following general formula: [ka]

[0071] where EG is a first unspecified terminal group, B is an unspecified bridging group, EG * is a second unspecified end group, and EG, B and EG * is determined by the synthesis method used to produce the PEBA copolymer, where n2 is the length of the polyamide block, x3 is the length of the amide moiety within the polyamide block, m1 is the length of the poly(ether) block, y3 is the length of the ether moiety within the poly(ether) block, and p is the length of the PEBA copolymer and indicates the total number of polyamide and polyether blocks. In some embodiments of the present disclosure, the PEBA copolymer can be represented by the following general formula: [ka]

[0072] Here, n2 represents the length of the polyamide block, x3 represents the length of the amide component in the polyamide block, m1 represents the length of the poly(ether) block, y3 represents the length of the ether component in the poly(ether) block, p represents the length of the PEBA copolymer, and represents the total number of polyamide and polyether blocks.

[0073] The polyamide blocks in the PEBA copolymer are derived from polyamide-12 (PA-12), polyamide-11 (PA-11), polyamide-6 (PA-6), or polyamide-66 (PA-66).

[0074] The weight average molecular weight (e.g., Mw and Mn) of the PEBA copolymer can be measured, for example, by gel permeation chromatography (i.e., size exclusion chromatography) using narrow molecular weight polymer standards using techniques known in the art.

[0075] In embodiments, the number average molecular weight Mn of the polyamide blocks in the PEBA copolymer is from about 100 to about 15,000 g / mol, or from about 300 to about 15,000 g / mol, or from about 600 to about 10,000 g / mol, or from about 600 to about 5,000 g / mol. The number average molecular weight Mn of the polyether blocks in the PEBA copolymer is from about 100 to about 15,000 g / mol, from about 100 to about 10,000 g / mol, from about 100 to about 6,000 g / mol, from about 100 to about 3,000 g / mol, from about 200 to about 6,000 g / mol, from about 200 to about 3,000 g / mol, from about 250 to about 2,000 g / mol, from about 750 to about 3,500 g / mol, or from about 1,000 to about 3,000 g / mol.

[0076] The PEBA copolymer has a number average molecular weight, Mn, of 10,000 to 500,000 g / mol, including any subrange and any number within this range. For example, in embodiments of the present disclosure, the number average molecular weight Mn of the PEBA copolymer is from 10,000 to 400,000 g / mol, or from 10,000 to 300,000 g / mol, or from 10,000 to 250,000 g / mol, or from 15,000 to 300,000 g / mol, or from 20,000 to 300,000 g / mol, or from 15,000 to 200,000 g / mol, or from 20,000 to 200,000 g / mol, or from 30,000 to 250,000 g / mol, or from about 25,000 to about 75,000 g / mol, or from about 50,000 to about 75,000 g / mol, or from about 100,000 to about 150,000 g / mol. The PEBA copolymer has a number average molecular weight Mn of at least 10,000 g / mol, at least 20,000 g / mol, at least 25,000 g / mol, greater than 25,000 g / mol, at least 30,000 g / mol, greater than 30,000 g / mol, at least 35,000 g / mol, greater than 35,000 g / mol, at least 50,000 g / mol, or greater than 50,000 g / mol.

[0077] In embodiments, the weight average molecular weight, Mw, of the PEBA copolymer is from 25,000 to 500,000 g / mol, including subranges and any number within this range. For example, in embodiments of the present disclosure, the weight average molecular weight, Mw, of the PEBA copolymer is from about 100,000 to about 250,000 g / mol, or from about 100,000 to about 150,000 g / mol, or from about 125,000 to about 150,000 g / mol. The polyamide and polyether blocks within the PEBA copolymer may be randomly distributed.

[0078] The PEBA copolymer may comprise a polyamide block and a polyether block, with the polyamide block comprising at least 50% by weight of the copolymer. The PEBA copolymer may comprise a polyamide block and a polyether block, with the polyether block comprising at least 50% by weight of the copolymer. Furthermore, the PEBA copolymer may comprise a polyamide block and a polyether block, with the molar ratio of the polyamide block to the polyether block being in the range of 1:3 to 3:1, or 1:2 to 2:1, or 3:2 to 1:3, or 2:3 to 3:1, or about 1:1.

[0079] PEBA copolymers having polyamide blocks and polyether blocks can be prepared by reacting the polyamide and polyether block precursors described above. For example, a lactam, a polyether diol, and a chain-limiting diacid can be reacted together in the presence of a small amount of water to obtain PEBA copolymers having polyamide blocks and polyether blocks of variable length and statistically random distribution within the block copolymer chains. The polyether blocks may be derived from poly(oxyethylene), poly(oxypropylene), or poly(tetramethylene ether) glycol, each of which may be naturally co-condensed with polyamide blocks containing carboxylic acid chain ends. A chain limiter may also be present during the polycondensation reaction to provide a PEBA copolymer containing polyamide and polyether blocks randomly distributed within the block copolymer. The polyether blocks are derived from poly(oxyethylene), poly(oxypropylene), or poly(tetramethylene ether) glycols, which are first converted to polyether diamines by amination and then co-condensed with polyamide blocks containing carboxylic acid chain ends. A chain limiter can also be present during the polycondensation reaction to provide PEBA copolymers containing polyamide and polyether blocks randomly distributed within the block copolymer. The polyether blocks can be derived from poly(oxyethylene), also known as polyethylene glycol (PEG). The polyether blocks can be derived from poly(oxypropylene), also known as polypropylene glycol (PPG). The polyether blocks may be derived from poly(tetramethylene ether) glycol (PTMG), also known as polytetramethylene oxide (PTMEO) or polytetrahydrofuran (PTHF).

[0080] The PEBA copolymer comprises i) polyamide blocks selected from polyamide-12 (PA-12), polyamide-11 (PA-11), polyamide-6 (PA-6), or mixtures thereof, and ii) polyether blocks selected from polyethylene glycol (PEG), polypropylene glycol (PPG), polytetrahydrofuran (PTHF), or mixtures thereof.

[0081] The PEBA copolymer comprises i) a polyamide block selected from polyamide-12 (PA-12), polyamide-11 (PA-11), polyamide-6 (PA-6), or a mixture thereof, and ii) a polyether block that is polyethylene glycol (PEG). In one embodiment of the present disclosure, the PEBA copolymer comprises i) a polyamide block that is polyamide-12 (PA-12), and ii) a polyether block that is polyethylene glycol (PEG).

[0082] The PEBA copolymer contains 10 to 20 polyamide blocks and 10 to 20 polyether blocks.

[0083] The PEBA copolymer contains only one type of polyamide block and one type of polyether block.

[0084] The PEBA copolymer comprises i) a polyamide block which is polyamide-12 (PA-12) and ii) a polyether block which is polyethylene glycol (PEG), wherein the polyamide-12 block accounts for approximately 30% to 70% by weight of the copolymer, and the polyethylene glycol block accounts for approximately 70% to 30% by weight of the copolymer.

[0085] The PEBA copolymer comprises i) a polyamide block which is polyamide-12 (PA-12), and ii) a polyether block which is polyethylene glycol (PEG), wherein the polyamide-12 block accounts for approximately 40% to 60% by weight of the copolymer, and the polyethylene glycol block accounts for approximately 60% to 40% by weight of the copolymer.

[0086] The PEBA copolymer comprises i) a polyamide block that is polyamide-12 (PA-12) and ii) a polyether block that is polyethylene glycol (PEG), where the polyamide-12 block represents about 45% by weight of the copolymer and the polyethylene glycol block represents about 55% by weight of the copolymer.

[0087] The PEBA copolymer comprises i) 10 to 20 polyamide blocks that are polyamide-12 (PA-12), and ii) 10 to 20 polyether blocks that are polyethylene glycol (PEG).

[0088] The PEBA copolymer comprises i) a polyamide block which is polyamide-12 (PA-12), and ii) a polyether block which is polyethylene glycol (PEG), and has a number average molecular weight Mn of about 25,000 to about 75,000 g / mol.

[0089] The PEBA copolymer comprises i) a polyamide block that is polyamide-12 (PA-12) and ii) a polyether block that is polyethylene glycol (PEG), and has a number average molecular weight Mn of about 50,000 to about 75,000 g / mol. The PEBA copolymer comprises i) a polyamide block that is polyamide-12 (PA-12) and ii) a polyether block that is polyethylene glycol (PEG), and has a number average molecular weight Mn of about 66,100 g / mol.

[0090] The PEBA copolymer contains i) a polyamide block which is polyamide-12 (PA-12) and ii) a polyether block which is polyethylene glycol (PEG), and has a weight average molecular weight Mw of about 100,000 to about 150,000 g / mol.

[0091] The PEBA copolymer contains i) a polyamide block which is polyamide-12 (PA-12) and ii) a polyether block which is polyethylene glycol (PEG), and has a weight average molecular weight Mw of about 125,000 to about 150,000 g / mol.

[0092] The PEBA copolymer comprises i) a polyamide block which is polyamide-12 (PA-12) and ii) a polyether block which is polyethylene glycol (PEG), and has a weight average molecular weight Mw of about 134,000 g / mol.

[0093] In one embodiment of the present disclosure, the PEBA copolymer comprises i) a polyamide block that is polyamide-6 (PA-6), and ii) a polyether block that is polyethylene glycol (PEG). The PEBA copolymer comprises i) a polyamide block that is polyamide-6 (PA-6) and ii) a polyether block that is polyethylene glycol (PEG), where the polyamide-6 block represents about 30% to 60% by weight of the copolymer and the polyethylene glycol block represents about 70% to 40% by weight of the copolymer.

[0094] The PEBA copolymer comprises i) a polyamide block that is polyamide-6 (PA-6) and ii) a polyether block that is polyethylene glycol (PEG), where the polyamide-6 block represents about 50% to 35% by weight of the copolymer and the polyethylene glycol block represents about 50% to 65% by weight of the copolymer.

[0095] The PEBA copolymer comprises i) 10 to 20 polyamide blocks that are polyamide-6 (PA-6), and ii) 10 to 20 polyether blocks that are polyethylene glycol (PEG).

[0096] The PEBA copolymer includes i) a polyamide block that is polyamide-11 (PA-11) and ii) a polyether block that is polyethylene glycol (PEG). In one embodiment of the present disclosure, the PEBA copolymer includes i) a polyamide block that is polyamide-12 (PA-12) and ii) a polyether block that is polytetrahydrofuran (PTHF).

[0097] The PEBA copolymer comprises i) a polyamide block that is polyamide-12 (PA-12), and ii) a polyether block that is polytetrahydrofuran (PTHF), wherein the polyamide-12 block represents about 75% to 10% by weight of the copolymer and the polytetrahydrofuran block represents about 25% to 90% by weight of the copolymer.

[0098] The PEBA copolymer comprises i) a polyamide block that is polyamide-12 (PA-12), and ii) a polyether block that is polytetrahydrofuran (PTHF), wherein the polyamide-12 block represents about 80% to 60% by weight of the copolymer and the polytetrahydrofuran block represents about 20% to 40% by weight of the copolymer.

[0099] The PEBA copolymer comprises i) a polyamide block that is polyamide-12 (PA-12), and ii) a polyether block that is polytetrahydrofuran (PTHF), wherein the polyamide-12 block represents about 40% to 60% by weight of the copolymer and the polytetrahydrofuran block represents about 60% to 40% by weight of the copolymer.

[0100] The PEBA copolymer comprises i) a polyamide block that is polyamide-12 (PA-12), and ii) a polyether block that is polytetrahydrofuran (PTHF), wherein the polyamide-12 block represents about 30% to 10% by weight of the copolymer and the polytetrahydrofuran block represents about 70% to 90% by weight of the copolymer. The PEBA copolymer comprises i) 10 to 20 polyamide blocks that are polyamide-12 (PA-12), and ii) 10 to 20 polyether blocks that are polytetrahydrofuran (PTHF).

[0101] The PEBA copolymer comprises i) a polyamide block which is polyamide-12 (PA-12) and ii) a polyether block which is polytetrahydrofuran (PTHF), and has a number average molecular weight Mn of about 25,000 to about 75,000 g / mol. The PEBA copolymer comprises i) a polyamide block that is polyamide-12 (PA-12) and ii) a polyether block that is polytetrahydrofuran (PTHF), and has a number average molecular weight Mn of about 40,000 to about 60,000 g / mol. In an embodiment of the present disclosure, the PEBA copolymer comprises i) a polyamide block that is polyamide-12 (PA-12) and ii) a polyether block that is polytetrahydrofuran (PTHF), and has a number average molecular weight Mn of about 50,000 g / mol.

[0102] The PEBA copolymer includes i) a polyamide block that is polyamide-6 (PA-6), and ii) a polyether block that is polytetrahydrofuran (PTHF). The PEBA copolymer includes i) a polyamide block that is polyamide-11 (PA-11), and ii) a polyether block that is polytetrahydrofuran (PTHF). The PEBA copolymer is a commercially available elastomer sold under the trade name PEBAX®.

[0103] The PEBA copolymer is a commercially available elastomer selected from the group consisting of: PEBAX 2533 SA 01, PEBAX 2533 SA 01 MED, PEBAX 2533 SD 02, PEBAX 3533 SA 01, PEBAX 3533 SA 01 MED, PEBAX 3533 SP01, PEBAX 4011, PEBAX 4033 SA 01, PEBAX 4033 SA 01 MED, PEBAX 4033 SP01, PEBAX 4533 SA 01, PEBAX 4533 SA 01 MED, PEBAX 4533 SP01, PEBAX 5513 SA 01, PEBAX 5513 SP01, PEBAX 5533 SA 01, PEBAX 5533 SA 01 MED, PEBAX 5533 SN 70 BLACK, PEBAX 5533 SP01, PEBAX SA 01, PEBAX 6333 SA 01 MED, PEBAX SP01, PEBAX 6333 SP01, PEBAX 6333 SA 01, PEBAX, PEBAX 3533 SA 01, PEBAX 3533 SA 01 MED, PEBAX 3533 SP01, PEBAX 4011 SA 01, PEBAX 4033 SA 01 MED, PEBAX 4033 SP01, PEBAX 4033 SA 01 MED, PEBAX Clear 2533, PEBAX ES 2533 UV, PEBAX MH 2533, PEBAX MH2030, PEBAX MV 5513 SA 01, PEBAX MV 5513 Examples of suitable rubber additives include PEBAX SA 01 MED, PEBAX MV 5533 SP01, PEBAX MV 5533, PEBAX MV 5533 SP01, PEBAX RNEW® 30R51 SA 01, PEBAX RNEW 35R53 SP01, PEBAX RNEW 70R53 SP01, PEBAX RNEW 55R53 SP01, PEBAX RNEW 63R53 SP01, PEBAX RNEW 70R53 SP01, PEBAX RNEW 70R53 SP01, PEBAX, PEBAX RNEW 72R53 SP01, PEBAX RNEW 80R53 SP 02, and mixtures thereof. The PEBA copolymer is a commercially available elastomer sold under the trade name VESTAMID® or VESTAMID E.

[0104] The PEBA copolymer is a commercially available elastomer selected from the group consisting of VESTAMID D, VESTAMID DX, VESTAMID E, VESTAMID EX, VESTAMID Care, VESTAMID Care ML, VESTAMID Care ME, VESTAMID Care ME-B, VESTAMID L, VESTAMID LX, VESTAMID NRG, VESTAMID Terra, VESTAMID X, and mixtures thereof, with Pebax MV1072 being preferred.

[0105] The PEBA copolymers can be used in the form of a semi-solid or viscous liquid, or as a powder, pellets, or granules.

[0106] In the processing aid of the present disclosure, the content of the synergist is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less. In the processing aid of the present disclosure, the content of the synergist may preferably be 0.1% by mass or more, 0.5% by mass or more, or 1% by mass or more, and may be 40% by mass or less, 30% by mass or less, or 20% by mass or less.

[0107] In the processing aid of the present disclosure, the mass ratio of the ethylene-vinyl alcohol copolymer to the synergist (ethylene-vinyl alcohol copolymer:synergist) is preferably 99.9:0.1 to 10:90, more preferably 99.5:0.5 to 70:30, even more preferably 99:1 to 85:15, and particularly preferably 98:2 to 92:8.

[0108] In the processing aid of the present disclosure, the total content of the ethylene-vinyl alcohol copolymer and the synergist is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 85% by mass or more, and particularly preferably 90% by mass. In the processing aid of the present disclosure, the total content of the ethylene-vinyl alcohol copolymer and the synergist may be 80% by mass or more, 90% by mass or more, 95% by mass or more, or even 100% by mass.

[0109] The processing aid of the present disclosure may contain components other than the ethylene-vinyl alcohol copolymer and the synergist.

[0110] The processing aid of the present disclosure is preferably substantially free of fluorine. "Substantially free of fluorine" means that the fluorine content in the processing aid is 10 ppm or less (preferably 1 ppm or less, more preferably 0.1 ppm or less). It is more preferable that the processing aid of the present disclosure is fluorine-free (the fluorine content is 0% by mass).

[0111] The processing aid of the present disclosure may be a masterbatch further comprising a thermoplastic resin (A).

[0112] Examples of the thermoplastic resin (A) include polyolefin polymers (polyethylene (PE)-polypropylene (PP)-ethylene-propylene copolymers), polystyrene (PS), AS (acrylonitrile styrene) resins (AS), ABS (acrylonitrile butadiene styrene) resins (ABS), methacrylic resins (PMMA), polymethylpentene (PMP), butadiene resins (BDR), polybutene-1 (PB-1), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), polymethacrylic styrene (MS), ethylene-vinyl acetate copolymers (EVA), ethylene-vinyl alcohol copolymers, and polyvinyl chloride (PVC). These may be used alone or in combination of two or more. Polyolefin polymers (polyolefin resins) are preferred because they provide a better effect of improving processability.

[0113] Among polyolefin polymers, for example, homopolymers (e.g., homopolymers of C2 to C10 α-olefins, preferably C2 to C6 α-olefins) can be mentioned. Specific examples of homopolymers include homopolyethylene and polypropylene (hPP). For example, homopolyethylene can be produced by free radical polymerization in a high-pressure process, and is typically a highly branched ethylene homopolymer, often known as LDPE (low-density polyethylene), with a density of 0.945 g / cm. 3 Less than 0.935 g / cm 3 or less, e.g., 0.900, 0.905, or 0.910 g / cm 3 to 0.920, 0.925, 0.927, 0.930, 0.935, or 0.945 g / cm 3 Unless otherwise specified herein, all polymer density values ​​are determined in accordance with ASTM D1505. Samples are molded under ASTM D4703-10a, Procedure C, and conditioned under ASTM D618-08 (23±2°C and 50±10% relative humidity) for 40 hours before testing.

[0114] In another example, ethylene monomer can be polymerized using known gas, slurry, and / or solution phase polymerizations, e.g., catalysts such as chromium-based catalysts, or single-site catalysts such as Ziegler-Natta and / or metallocene catalysts, all of which are well known in the polymerization art and will not be discussed further herein. When a more highly linear ethylene homopolymer is produced (e.g., using gas or slurry phase polymerization with any of the above catalysts), it is referred to as HDPE (high density polyethylene), and typically has a density of 0.945 to 0.970 g / cm. 3 In the range of 0.945 g / cm 3 It has a density of more than 10 ...

[0115] Further exemplary polymers include copolymers of two or more C2-C40 α-olefins, such as C2-C20 α-olefins, such as ethylene-α-olefin copolymers, or propylene-α-olefin copolymers (e.g., propylene-ethylene copolymers or propylene-ethylene-diene terpolymers (sometimes known as EPDM or PEDM)). Specific examples contemplated herein include copolymers of ethylene and one or more C3-C20 α-olefin comonomers, such as C4-C12 α-olefin comonomers (1-butene, 1-hexene, 1-octene, or mixtures of two or more thereof are preferred in various embodiments). The ethylene copolymer (e.g., a copolymer of ethylene and one or more C3-C20 α-olefins) can comprise ethylene-derived units in an amount of at least 90, 94, 95, or 96 wt% (e.g., 80, 85, 90, 80, 85, 93, 93, 95, 96, or 97 wt%) to an upper value of 94, 95, 95.5, 91, 92, 97, 94, 97.5, or 98 wt%), including a range from any lower value to any upper value, based on the total amount of ethylene-derived units and comonomer-derived units. For example, the ethylene copolymer can comprise ethylene-derived units in an amount of at least 96 wt%, 94, 95, 95, or 96.5 wt% (e.g., 80, 85, 90, 80, 85, 93, 93, 95, 96, or 97 wt%) to an upper value of 94, 95, 95.5, 91, 92, 97, 94, 97.5, or 98 wt%), based on the total amount of ethylene-derived units and comonomer-derived units. In some cases, the copolymer may contain 94 or 95% to 97 or 98% by weight of ethylene-derived units. The balance of the copolymer (based on ethylene-derived units and comonomer-derived units) consists of comonomer-derived units. For example, comonomer units (e.g., units derived from C2 to C20 α-olefins, such as units derived from butene, hexene, and / or octene) may be present in the ethylene copolymer from a low of 2, 2.5, 3, 3.5, 4, 4.5, 5, or 6% by weight to a high of 3, 4, 5, 6, 7, 8, 9, 10, 15, or 20% by weight, ranging from the low value to the contemplated high value (provided the high value is greater than the low value).

[0116] While several suitable comonomers are known for ethylene-based, propylene-based, or other α-olefin-based copolymers, other α-olefin comonomers are contemplated in various embodiments. For example, the α-olefin comonomers may be linear or branched, and two or more comonomers may be used if desired. Examples of suitable comonomers include linear C3-C20 α-olefins (such as butene, hexene, and octene, as previously mentioned) and α-olefins having one or more C1-C3 alkyl branched or aryl groups. For example, comonomers include propylene; 3-methyl-1-butene; 3,3-dimethyl-1-butene; 1-pentene; 1-pentene having one or more methyl, ethyl or propyl substituents; 1-hexene having one or more methyl, ethyl or propyl substituents; 1-heptene having one or more methyl, ethyl or propyl substituents; 1-octene having one or more methyl, ethyl or propyl substituents; 1-nonene having one or more methyl, ethyl or propyl substituents; ethyl, methyl or dimethyl substituted 1-decene; 1-dodecene; and styrene.The above list of comonomers is merely illustrative and is not intended to be limiting.In some embodiments, the comonomer includes propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-octene and styrene.

[0117] In certain embodiments, the polymer can include or be (in accordance with those described above) an ethylene copolymer. The ethylene copolymer can be produced by gas, slurry, or solution phase polymerization, with some particularly preferred ethylene copolymers being produced by gas or slurry phase polymerization. A particular example is linear low density polyethylene (LLDPE), a copolymer of ethylene and one or more α-olefins, polymerized in the presence of one or more single-site catalysts, such as one or more Ziegler-Natta catalysts, one or more metallocene catalysts, and combinations thereof. Such LLDPEs have viscosity profiles of 0.900, 0.905, 0.907, 0.910 g / cm. 3from low concentrations of 0.920, 0.925, 0.930, 0.935, 0.940, or 0.945 g / cm 3 The density of LLDPE can be in the high concentration range of 0.902 to 0.945, 0.906 to 0.932, or 0.908 to 0.926. LLDPE can be distinguished from the LDPEs described above in several respects, many of which are well known in the art, including the degree of branching (often little, if any) in the produced polymer, noting that LLDPE has substantially less long-chain branching. In certain embodiments, the polymer of the polymer composition is or comprises a metallocene-catalyzed LLDPE (mLLDPE). In yet other embodiments, the polymer of the polymer composition is or comprises a Ziegler-Natta-catalyzed LLDPE (ZN-LLDPE).

[0118] The density of the polymer may also be, in some embodiments, from 0.905 to 0.945 g / cm 3 in the range of, for example, 0.905, 0.907, 0.908, 0.910, 0.911, 0.912, 0.913, 0.914, or 0.915 g / cm 3 from the lower of 0.916, 0.917, 0.918, 0.919, 0.920, 0.924, 0.926, 0.930, 0.935, 0.940, or 0.945 g / cm 3 to any higher value, the range being from the lower to higher values ​​contemplated herein (e.g., 0.910 to 0.925 or 0.935 g / cm 3 , e.g., 0.912 to 0.925 or 0.915 to 0.918 g / cm 3 In yet another embodiment, the polymer has a density of 0.945 g / cm 3 to 0.970 g / cm 3 It may also be of higher density (eg HDPE) having a density in the range

[0119] Furthermore, the rheological properties of the polymer can influence the processing aid composition to form the molding. Generally, it is preferred that the PPA composition be used in polymers having a melt index (MI or I2 measured according to ASTM D1238 at 190°C under a 2.16 kg load) of 1.5 g / 2.0 min or less, preferably 2.5 g / 3.0 min or less, such as in the range of 0.1, 0.2, or 0.5 g / 10 min to 1.0, 1.2, 5.0, 10, 2.5, 10, 4.0, or 5.0 g / 10 min. The melt index ratio (MIR) (MIR is defined herein as the ratio of the high load melt index (HLMI) (measured per ASTM D1238 at 190°C under a 21.6 kg load) to the melt index, or HLMI / MI), in some embodiment polymers can have an MIR generally within the range of 10, 12, or 15 to 19, 20, 21, 22, 25, 27, 30, 35, 40, 45, 50, 60, 65, 70, 75, 80, 85, 90, 95, or 100. Optionally, the MI in such polymers can be less than 1.5 g / 10 min, such as 1.0 g / 10 min or less (e.g., 0.1, 0.2, or 0.5 g / 10 min to 1.0; or less than any of 1.1, 1.2, 1.3, 1.4, or 1.5 g / 10 min).

[0120] The LLDPE is preferably at least one selected from the group consisting of Ziegler-Natta catalyst-type LLDPE and metallocene catalyst-type LLDPE, with metallocene catalyst-type LLDPE being particularly preferred.

[0121] The thermoplastic resin (A) may be crystalline or non-crystalline. When the thermoplastic resin (A) is crystalline, it preferably has a melting point of 80 to 300° C., more preferably 100 to 200° C. The non-crystalline thermoplastic resin (A) preferably has a processing temperature approximately equal to that of the crystalline thermoplastic resin (A) having a specified melting point range.

[0122] When the processing aid of the present disclosure is in the form of a masterbatch, the mass ratio of the thermoplastic resin (A) to the ethylene-vinyl alcohol copolymer (thermoplastic resin (A):ethylene-vinyl alcohol copolymer) is preferably 99:1 to 1:99. The mass ratio is more preferably 97:3 to 50:50, even more preferably 95:5 to 60:40, and particularly preferably 92:8 to 70:30. The mass ratio may be 99:1 to 40:60, 95:5 to 50:50, 93:7 to 25:75, 90:10 to 60:40, or 85:15 to 70:30.

[0123] When the processing aid of the present disclosure is a masterbatch, the total content of the thermoplastic resin (A) and the ethylene-vinyl alcohol copolymer is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more. The upper limit is not particularly limited, and may be 100% by mass.

[0124] The melt flow rate (MFR) of the processing aid of the present disclosure is preferably 0.01 g / 10 min or more, more preferably 0.1 g / 10 min or more, even more preferably 1.0 g / 10 min or more, and is preferably 100 g / 10 min or less, more preferably 50 g / 10 min or less, even more preferably 20 g / 10 min or less. If it is within the above range, the effect of improving processability will be better. In this specification, MFR is measured in accordance with ASTM D 1238 under conditions of 190°C and a load of 2.16 kgf.

[0125] The processing aid of the present disclosure may contain components other than the thermoplastic resin (A) and the ethylene-vinyl alcohol copolymer agent, as long as the object of the present disclosure is not impaired.

[0126] The moisture content of the processing aid of the present disclosure may be 0.3% by mass or less, preferably 0.2% by mass or less, and more preferably 0.1% by mass or less. There is no particular lower limit, and it may be 0% by mass.

[0127] In this specification, the water content is measured by the following method. The mass of the processing aid is measured before and after heating at 130°C for 24 hours, and calculated according to the following formula. Three samples are taken, and the average value is calculated for each. Moisture content (mass%) = [(mass of processing aid before heating (g)) - (mass of processing aid after heating (g))] / (mass of processing aid before heating (g)) × 100

[0128] There are no particular limitations on the method for obtaining a processing aid having a moisture content within the above range. For example, the processing aid may be prepared under dry conditions using materials with a low moisture content, or the processing aid may be prepared using ordinary materials and conditions, and then the moisture may be removed by heat treatment or the like.

[0129] The processing aid of the present disclosure preferably comprises a lubricant (A).

[0130] The lubricant (A) is an additive that reduces friction and improves slipperiness, and examples thereof include waxes, alcohols, surfactants, etc. These may be used singly or in combination of two or more. The lubricant (A) is preferably at least one selected from the group consisting of waxes, alcohols, and surfactants, more preferably at least one selected from the group consisting of waxes and surfactants, and even more preferably a surfactant.

[0131] Examples of the waxes include pure hydrocarbon waxes such as liquid paraffin, natural paraffin, microwax, synthetic paraffin, polyethylene wax, and polyethylene / polypropylene wax; fatty acid waxes such as higher fatty acids and oxyfatty acids; fatty acid amide waxes such as fatty acid amides and bisfatty acid amides; and fatty acid ester waxes such as lower alcohol esters of fatty acids, polyhydric alcohol esters of fatty acids such as glycerides, polyglycol esters of fatty acids, and fatty alcohol esters of fatty acids (ester waxes). Of these, pure hydrocarbon waxes and fatty acid ester waxes are preferred, and pure hydrocarbon waxes are more preferred. Preferred pure hydrocarbon waxes are polyethylene wax and polyethylene / polypropylene wax, and polyethylene wax is more preferred. Preferred fatty acid ester waxes are adipic acid esters and glycerin fatty acid esters. Examples of the polyethylene wax include ordinary polymerization polyethylene wax, metallocene catalyst polyethylene wax, acid-modified polyethylene wax, oxidation type (slight oxidation, high acid value) polyethylene wax, aromatic monomer-modified polyethylene wax, etc. Acid-modified types include those copolymerized with vinyl carboxylic acids such as acrylic acid and methacrylic acid, oxidation types include those obtained by air oxidation or thermal decomposition of polyethylene, and aromatic monomer-modified polyethylene wax includes those modified by graft polymerization of styrene monomer.

[0132] Examples of fatty acid ester waxes include phthalate esters, dimethyl and diethyl succinate and related esters, glycerol monoacetate, glycerol diacetate, glycerol triacetate, glycerol monoacid esters, citrate esters, adipate esters, stearates, oleate esters, etc. These may be used alone or in combination of two or more kinds.

[0133] Examples of adipic acid esters include adipic acid diesters. Specific examples include dimethyl adipate, dibutyl adipate, bis[2-(2-methoxyethoxy)ethyl]adipate, bis(butyldiglycol)adipate, bis(methyldiglycol)adipate, benzyl[2-(2-methoxyethoxy)ethyl]adipate, di-n-butyl adipate, dioctyl adipate, methyldiglycol butyldiglycol adipate, benzylmethylglycol adipate, benzylbutyldiglycol adipate, and diisononyl phthalate. These may be used alone or in combination of two or more. Among these, diisononyl phthalate and dioctyl adipate are preferred.

[0134] Glycerin fatty acid esters include glycerin monostearate, glycerin monobehenate, glycerin mono 12-hydroxystearate, glycerin monooleate, glycerin monocaprylate, glycerin monocaprate, glycerin monolaurate, glycerin diacetomonolaurate, succinic acid fatty acid monoglyceride, citric acid fatty acid monoglyceride, diacetyltartaric acid fatty acid monoglyceride, diglycerin laurate, diglycerin stearate, diglycerin oleate, diglycerin mono ... Examples include glycerin monolaurate, diglycerin monomyristate, diglycerin monostearate, diglycerin monooleate, tetraglycerin stearate, decaglycerin laurate, decaglycerin stearate, decaglycerin oleate, polyglycerin polyricinoleate, propylene glycol monolaurate, propylene glycol monopalmitate, propylene glycol monostearate, propylene glycol monooleate, and propylene glycol monobehenate. These may be used alone or in combination of two or more. Among these, glycerin diacetomonolaurate and decaglycerin stearate are preferred.

[0135] The acid value of the waxes is preferably 40 mgKOH / g or less, more preferably 30 mgKOH / g or less, and even more preferably 20 mgKOH / g or less. The lower limit is not particularly limited, and may be 0 mgKOH / g. Within the above range, the effect of improving processability is more excellent. The acid value is the number of milligrams of potassium hydroxide required to neutralize the free acid contained in 1 g of wax. The acid value of waxes can be measured, for example, by a general neutralization titration method (JIS K 0070:1992).

[0136] The melting point of the waxes is preferably 40° C. or higher, more preferably 60° C. or higher, and even more preferably 80° C. or higher, and is preferably 200° C. or lower, more preferably 160° C. or lower, and even more preferably 130° C. or lower. Within the above range, the effect of improving processability is better. In this specification, the melting point is the temperature corresponding to the maximum value in the heat of fusion curve when the temperature is increased at a rate of 10°C / min using a differential scanning calorimetry (DSC) device.

[0137] The melt viscosity of the waxes at 140°C is preferably 20 mPa·s or more, more preferably 40 mPa·s or more, and even more preferably 60 mPa·s or more, and is preferably 500 mPa·s or less, more preferably 400 mPa·s or less, and more preferably 350 mPa·s or less. Within the above ranges, the processability can be improved. The melt viscosity was measured in accordance with ISO 11443 using a flow tester (manufactured by Shimadzu Corporation) and a 2φ-8L die, with a 2g sample preheated to 140°C for 5 minutes and maintained at the above temperature under a load of 0.7 MPa.

[0138] Examples of the alcohols include fatty alcohols such as higher alcohols, and polyhydric alcohols such as polyglycols and polyglycerols. These may be used alone or in combination of two or more.

[0139] Examples of fatty alcohols include lauryl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, oleyl alcohol, behenyl alcohol, etc. These may be used alone or in combination of two or more.

[0140] Examples of the surfactant include anionic surfactants such as metal soaps and ammonium salts; cationic surfactants such as alkylamine salts and quaternary ammonium salts; nonionic surfactants such as esters, ethers, ester / ethers, and amides; and amphoteric surfactants such as aminocarboxylates, alkylbetaines, and alkylimidazoline derivatives. Among these, anionic surfactants or nonionic surfactants are preferred. As anionic surfactants, metal soaps are preferred, and specifically, carboxylates, sulfates, sulfonates, and phosphate ester salts are preferred. As nonionic surfactants, ester / ethers are preferred, and specifically, sugar surfactants are preferred.

[0141] Examples of the metal soap include fatty acid salts, polysulfonates, polycarboxylates, alkyl sulfates, alkylaryl sulfonates, alkylnaphthalenesulfonates, dialkylsulfonates, dialkylsulfosuccinates, alkyl phosphates, polyoxyethylene alkyl ether sulfates, polyoxyethylene alkylaryl ether sulfates, and polyoxyethylene alkyl phosphate sulfonates, and specific examples include sodium dodecylbenzenesulfonate, sodium lauryl sulfate, sodium polyoxyethylene lauryl ether sulfate, and polyoxyethylene nonylphenyl ether sulfate. These may be used alone or in combination of two or more.

[0142] The metal soap is preferably a compound represented by the following general formula (1): (R 5 COO) n1 M 1 (1) (In the general formula (1), R 5is a hydrogen atom or an alkyl group having 1 to 21 carbon atoms, n1 is an integer ranging from 1 to 4, and M 1 is lithium, sodium, potassium, rubidium, cesium, boron, magnesium, aluminum, calcium, manganese, iron, cobalt, nickel, tin, antimony, copper, silver, zinc, molybdenum, vanadium, strontium, zirconium, barium, bismuth, lead, gold, platinum, or a rare earth.

[0143] In the general formula (1), when n1 is an integer of 2 or more, a plurality of R 5 may be the same as or different from each other.

[0144] R 5 The alkyl group having 1 to 21 carbon atoms may be a linear alkyl group, a branched alkyl group, or may contain an alicyclic structure.

[0145] R 5 The alkyl group having 1 to 21 carbon atoms is used in the production of fatty acid metal salts. 5 It corresponds to a carboxylic acid residue obtained by removing the carboxyl group (COOH) from a carboxylic acid having 1 to 22 carbon atoms, represented by COOH. Examples of the carboxylic acid residue include acetic acid residue, propionic acid residue, butanoic acid residue, pentanoic acid residue, acrylic acid residue, methacrylic acid residue, octylic acid residue (2-ethylhexanoic acid residue), neodecanoic acid residue, naphthenic acid residue, isononanoic acid residue, tung oil acid residue, tall oil fatty acid residue, coconut oil fatty acid residue, soybean oil fatty acid residue, linseed oil fatty acid residue, safflower oil fatty acid residue, dehydrated castor oil fatty acid residue, tung oil fatty acid residue, lauric acid residue, myristic acid residue, palmitic acid residue, stearic acid residue, isostearic acid residue, oleic acid residue, and 12-hydroxystearic acid residue.

[0146] R 5 From the viewpoint of improving processability, the alkyl group having 1 to 21 carbon atoms is preferably an alkyl group having 12 to 21 carbon atoms, more preferably an alkyl group having 16 to 21 carbon atoms, and even more preferably a stearic acid residue or a 12-hydroxystearic acid residue.

[0147] M 1 is lithium, sodium, potassium, rubidium, cesium, boron, magnesium, aluminum, calcium, manganese, iron, cobalt, nickel, tin, antimony, copper, silver, zinc, molybdenum, vanadium, strontium, zirconium, barium, bismuth, lead, gold, or platinum.

[0148] n1 is M 1 is a value determined by the ionic valence of the metal atom, for example, M 1 If is boron, n1 is 3, and M 1 If is cobalt, n1 is 2.

[0149] The metal soap also includes a form of fatty acid metal borate, which is, for example, a compound represented by the following general formula (2): (R 6 COO-M 2 -O)3B (2) (In the general formula (2), R 6 is a hydrogen atom or an alkyl group having 1 to 21 carbon atoms, and M 2 is boron, magnesium, aluminum, calcium, manganese, iron, cobalt, nickel, tin, antimony, copper, zinc, molybdenum, vanadium, strontium, zirconium, barium, bismuth, lead, gold, or platinum.

[0150] In the general formula (2), R 6 The alkyl group having 1 to 21 carbon atoms is R 5 Similarly, in the general formula (2), M 2 The metal is M in the general formula (1). 1 It is the same as the metal.

[0151] The metal soap may be one type alone, or two or more types of metal soaps having different structures may be used.

[0152] Specific examples of the metal soap include metal salts of stearic acid, metal salts of hydroxystearic acid, etc. The metal soap is preferably at least one selected from the group consisting of metal salts of stearic acid and metal salts of hydroxystearic acid, and more preferably at least one selected from the group consisting of zinc stearate, magnesium hydroxystearate, and calcium stearate. Examples of the metal constituting the metal salt include zinc, magnesium, calcium, etc., and the metal salt is preferably at least one selected from the group consisting of zinc, magnesium, and calcium, and more preferably at least one selected from the group consisting of zinc and magnesium. The metal soap can be produced by a known method, or a commercially available product may be used.

[0153] Examples of the ammonium salt-based anionic surfactant include fatty acid ammonium salts. Examples include ammonium lauryl sulfate and ammonium polyoxyethylene lauryl ether sulfate. The anionic surfactant may be one type or two or more types.

[0154] Examples of cationic surfactants include alkylamine salts and quaternary ammonium salts, and specific examples include stearylamine acetate, trimethyl palmitic ammonium chloride, trimethyl tallow ammonium chloride, dimethyldioleyl ammonium chloride, methyl oleyl diethanol chloride, tetramethyl ammonium chloride, lauryl pyridinium chloride, lauryl pyridinium bromide, lauryl pyridinium disulfate, cetyl trimethyl ammonium chloride, cetyl pyridinium bromide, 4-alkyl mercaptopyridine, poly(vinylpyridine)-dodecyl bromide, and dodecyl benzyl triethyl ammonium chloride. The cationic surfactant may be one type only, or two or more types may be used.

[0155] Examples of amphoteric surfactants include aminocarboxylates, alkyl betaines, and alkyl imidazoline derivatives, and specific examples include lauric acid amidopropyl betaine. The amphoteric surfactants may be used alone or in combination of two or more.

[0156] Examples of ether-type nonionic surfactants include polyoxyethylene alkyl ethers, polyoxyalkylene derivatives, polyoxyethylene phenyl ethers, and alkyl allyl ethers, and specific examples include polyoxyethylene lauryl ether, polyoxyethylene oleyl ether, and polyoxyethylene octylphenyl ether. Examples of ester / ether type nonionic surfactants include sugar type surfactants, specifically sorbitan fatty acid esters, sorbitol, and polyoxyethylene sorbitan fatty acid esters. The nonionic surfactant may be used alone or in combination of two or more kinds.

[0157] Examples of the sugar surfactant include sucrose fatty acid esters, sorbitan acid esters, polysorbates, and the like. Specific examples of the sugar surfactant include sorbitan fatty acid esters such as sorbit monolaurate, sorbit monostearate, sorbit monooleate, sorbit trioleate, sorbit tristearate, and sorbit monoisostearate; sorbitan isostearate, sorbitan oleate, sorbitan caprylate, sorbitan dioleate, sorbitan distearate, sorbitan stearate, sorbitan sesquiisostearate, sorbitan sesquioleate, sesquioleate, sorbitan hydroxybenzo ... Sorbitan fatty acid esters such as sorbitan caprylate, sorbitan sesquistearate, sorbitan triisostearate, sorbitan trioleate, sorbitan tristearate, sorbitan palmitate, sorbitan coconutate, sorbitan laurate, and sorbitan oliveate; sucrose acetate isobutyrate, sucrose octaacetate, sucrose oleate, sucrose distearate, sucrose dilaurate, sucrose stearate, sucrose tetraisostearate, and tetraisostearate. Sucrose hydroxystearate, sucrose tristearate, sucrose tribehenate, sucrose trilaurate, sucrose tetrastearate triacetate, sucrose palmitate, sucrose hexaerucate, sucrose hexapalmitate, sucrose pentaerucate, sucrose pentahydroxystearate, sucrose polyoleate, sucrose polystearate, sucrose polysoybeanate, sucrose polypalmate, sucrose polybehenate, polylaurin Examples of the sucrose fatty acid esters include sucrose acid, sucrose polylinoleate, poly(cottonseed fatty acid) sucrose, sucrose myristate, sucrose coconut fatty acid, sucrose laurate, sucrose ricinoleate, sucrose benzoate, sucrose acetate distearate, and sucrose acetate stearate; and alkyl glucosides such as coconut oil fatty acid glucoside, lauryl glucoside, decyl glucoside, myristyl glucoside, palmityl glucoside, stearyl glucoside, and coco glucoside. These may be used alone or in combination of two or more.

[0158] As the sugar-type surfactant, sorbitan esters containing a non-polar carboxylic acid (lipophilic group) bonded to a polar sorbitan group (hydrophilic group) by an ester bond are preferred. Also preferred are polyoxyethylene derivatives of sorbitan esters and a plurality of polyoxyethylene oligomers chemically substituted on the sorbitan group.

[0159] These polyoxyethylene derivatives of sorbitan esters are called polysorbates. Specifically, the polyoxyethylene derivative of sorbitan ester (also referred to as polysorbate) has the formula (I):

Chemical formula

[0160] Here, one of R 7 ~R 10 is a linear fatty acid moiety, and the other three of R 7 ~R 10 are each hydrogen. Also, w1, x1, y1, z1 are integers such that 10 < w1 + x1 + y1 + z1 < 40. Preferably 15 < w1 + x1 + y1 + z1 < 25, and more preferably w1 + x1 + y1 + z1 = 20. Also, the linear fatty acid moiety is preferably (C=O)(CH2) a CH3. When the formula is (C=O)(CH2) b (CH)=(CH)(CH2) c CH3, the fatty acid moiety may alternatively contain a double bond along a hydrocarbon chain (i.e., may contain monounsaturation). Here, a is an integer from 10 to 25, preferably an integer from 12 to 18. Further, the linear fatty acid may contain an unsaturated bond. Also, b + c is an integer between 8 and 23, preferably an integer from 10 to 18. The number of unsaturated bonds may contain two or more unsaturations in the hydrocarbon chain, but the unsaturation is preferably 4 or less, more preferably 3 or less, and particularly preferably maintained at 0, 1, or

[0161] Specific examples of polysorbates include polysorbate 20 (polyoxyethylene (20) sorbitan monolaurate), polysorbate 40 (polyoxyethylene (20) sorbitan monopalmitate), polysorbate 60 (polyoxyethylene (20) sorbitan monostearate), and polysorbate 80 (polyoxyethylene (20) sorbitan monooleate).

[0162] The 20, 40, 60, and 80 following "polysorbate" indicate the fatty acid moiety (the "lipophilic group" of the molecule) attached to the polyoxyethylene sorbitan portion (the "hydrophilic group" of the molecule), with 20 being monolaurate, 40 being monopalmitic acid, 60 being monostearic acid, and 80 being monooleic acid (an example of a monounsaturated fatty acid moiety).

[0163] The name "Polysorbate #" refers to the addition of 20 oxyethylene moieties [-(CH2CH2O)-] to the sorbate.

[0164] In certain embodiments, the sugar surfactant can be or include one or more of polysorbate 20, polysorbate 40, polysorbate 60, and / or polysorbate 80. For example, the surfactant can be polysorbate 60 or can include other polysorbates.

[0165] Moreover, surfactants that are variants of the specific polysorbates mentioned above may be used in place of the polysorbates mentioned above. For example, with reference to formula (I), R 7 ~R 10 Two, three or all of the straight chain fatty acid moieties (R 7 ~R 10 The remainder, if any, may be hydrogen. An example of this compound is R 7 ~R 10 The three fatty acid moieties are stearic acid and R 7 ~R 10The other one includes polyoxyethylene sorbitan tristearate, in which hydrogen is present.

[0166] In the processing aid of the present disclosure, the content of the lubricant (A) is preferably 1% by mass or more, more preferably 2% by mass or more, even more preferably 4% by mass or more, and is preferably 98% by mass or less, more preferably 70% by mass or less, even more preferably 40% by mass or less, and most preferably 10% by mass or less.

[0167] In the processing aid of the present disclosure, the mass ratio of the ethylene-vinyl alcohol copolymer to the lubricant (A) (ethylene-vinyl alcohol copolymer:lubricant (A)) is preferably 99:1 to 1:99, more preferably 96:4 to 50:50, and most preferably 94:6 to 70:30.

[0168] The processing aid of the present disclosure preferably includes an antidegradant.

[0169] As the deterioration inhibitor, a compound containing at least one skeleton selected from the group consisting of a phenol skeleton and a phosphoric acid skeleton can be suitably used.

[0170] When the above-mentioned deterioration inhibitor has a phenol skeleton, the number of skeletons is not particularly limited, but is preferably 1 or more, more preferably 2 or more, even more preferably 3 or more, and particularly preferably 4 or more, and is preferably 100 or less, more preferably 10 or less, and even more preferably 6 or less.

[0171] Specific examples of the deterioration inhibitor having a phenol skeleton include 2,6-di-t-butyl-p-cresol, 2,6-di-t-butyl-4-ethylphenol, 2,6-dicyclohexyl-4-methylphenol, 2,6-diisopropyl-4-ethylphenol, 2,6-di-t-amyl-4-methylphenol, 2,6-di-t-octyl-4-n-propylphenol, 2,6-dicyclohexyl-4-n-octylphenol, 2-isopropyl-4-methyl-6-t-butylphenol, 2-t-butyl-4-ethyl-6-t -Octylphenol, 2-isobutyl-4-ethyl-6-t-hexylphenol, 2-cyclohexyl-4-n-butyl-6-isopropylphenol, styrenated mixed cresols, DL-α-tocopherol, stearyl β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2,6-di-t-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol, and other compounds having one phenol skeleton (monocyclic phenolic compounds); 2,2'-methylenebis(4-methyl -6-t-butylphenol), 4,4'-butylidenebis(3-methyl-6-t-butylphenol), 4,4'-thiobis(3-methyl-6-t-butylphenol), 2,2'-thiobis(4-methyl-6-t-butylphenol), 4,4'-methylenebis(2,6-di-t-butylphenol), 2,2'-methylenebis[6-(1-methylcyclohexyl)-p-cresol], 2,2'-ethylidenebis(4,6-di-t-butylphenol), 2,2'-butylidenebis(2-t-butyl-4-methylphenol), Compounds having two phenol skeletons (bicyclic phenol compounds), such as 3,6-dioxaoctamethylene bis[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionate], triethylene glycol bis[3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], and 2,2'-thiodiethylene bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate];1,1,3-Tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 1,3,5-tris(2,6-dimethyl-3-hydroxy-4-t-butylbenzyl)isocyanurate, 1,3,5-tris[(3,5-di-t-butyl-4-hydroxyphenyl)propionyloxyethyl]isocyanurate, tris(4-t-butyl-2,6-dimethyl-3-hydroxybenzyl)isocyanurate, 1,3,5-trimethyl-2,4,6- Examples of suitable phenol compounds include compounds having three phenolic skeletons (tricyclic phenol compounds), such as tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene; and compounds having four phenolic skeletons (tetracyclic phenol compounds), such as tetrakis[methylene-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane and pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]. Among these, tetracyclic phenol compounds are preferred, with tetrakis[methylene-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane and pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] being more preferred, and pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] being even more preferred.

[0172] The phosphate skeleton has a structure in which one to four O (oxygen atoms) are bonded to one P (phosphorus atom). Of these, one in which three O (oxygen atoms) are bonded to one P (phosphorus atom) is preferred.

[0173] When the anti-degradation agent has a phosphate skeleton, the number of skeletons is not particularly limited, but is preferably 1 or more, more preferably 2 or more, and even more preferably 3 or more, and is preferably 100 or less, more preferably 10 or less, and even more preferably 6 or less.

[0174] Specific examples of the deterioration inhibitor having a phosphate skeleton include: [ka] (However, R 1 is selected from the group consisting of linear or branched alkyl groups having 1 to 16 carbon atoms and aryl groups; R 1 may be the same or different), and P(OR 1 )3 (where R 1 is selected from the group consisting of linear or branched alkyl groups having 4 to 32 carbon atoms), more specific examples include trilauryl phosphite, triisodecyl phosphite, tridecyl phosphite, trihexadecyl phosphite, trioctadecyl phosphite, tribehenyl phosphite, triarachidyl phosphite, triceryl phosphite, trioleyl phosphite, tris(2-ethylhexyl) phosphite, diphosphates such as monostearyl phosphite (or its tautomer, monostearyl phosphonate) and distearyl phosphite (distearyl phosphonate), and high molecular weight homologues thereof, partially esterified phosphonic acid compounds, and alkali salts, alkaline earth salts, aluminum salts, or zinc salts thereof.

[0175] Examples of diphosphites include tetraethyl diphosphite and tetrapropyl diphosphite. Examples of triphosphites include the P,P'-bis(2-hydroxyethyl) ester of triphosphoric acid.

[0176] Oligophosphites and polyphosphites (oligomeric and polymeric phosphites) are described in, for example, WO 2011 / 102861, WO 2014 / 20519, WO 2020 / 123986, etc. Compounds described therein can also be used. Examples include the following compounds:

[0177] [ka]

[0178] Also included are phosphate esters, diphosphate esters, metaphosphate esters, polyphosphate esters derived from the above-mentioned phosphites, such as trilauryl phosphate, triisodecyl phosphate, tridecyl phosphate, trihexadecyl phosphate, trioctadecyl phosphate, tribehenyl phosphate, triarachidyl phosphate, triceryl phosphate, trioleyl phosphate, and the following structures and salts derived therefrom, as well as mixtures of at least two phosphate esters selected from the group consisting of monoalkyl phosphate esters, dialkyl phosphate esters, and trialkyl phosphate esters.

[0179] [ka]

[0180] In the case of the aforementioned phosphite derivatives, the phosphates, diphosphates, metaphosphates, and polyphosphates, the phosphorus atom is present in the +V oxidation state, rather than the +III oxidation state as in the phosphites.

[0181] The deterioration inhibitor having a phosphoric acid skeleton is preferably a phosphite. Examples of the phosphite include the following compounds:

[0182] [ka]

[0183] [ka]

[0184] [ka]

[0185] A particularly suitable phosphite is also tris(2,4-di-tert-butylphenyl) phosphite.

[0186] Specific examples of the deterioration inhibitor having a phenol skeleton and a phosphoric acid skeleton include phosphorus-containing phenol compounds such as calcium bis(3,5-di-t-butyl-4-hydroxybenzylphosphonate ethyl) and nickel bis(3,5-di-t-butyl-4-hydroxybenzylphosphonate ethyl).

[0187] The deterioration inhibitor may have only one of a phenol skeleton and a phosphate skeleton, or may have both a phenol skeleton and a phosphate skeleton, but is preferably one having only one of a phenol skeleton and a phosphate skeleton.

[0188] It is preferable to use a combination of the above-mentioned antidegradants, which have only a phenol skeleton (phenol-based antidegradants) and those which have only a phosphoric acid skeleton (phosphoric acid-based antidegradants), in order to improve pressure stability during extrusion.

[0189] When a phenolic deterioration inhibitor and a phosphoric acid deterioration inhibitor are used in combination as the deterioration inhibitor, the mass ratio thereof (phenolic deterioration inhibitor:phosphoric acid deterioration inhibitor) is preferably 20:80 to 80:20, more preferably 30:70 to 70:30, even more preferably 40:60 to 60:40, and particularly preferably 50:50.

[0190] In the processing aid of the present disclosure, the content of the anti-degradant is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, and is preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 60% by mass or less.

[0191] The processing aid of the present disclosure may be obtained, for example, by carrying out a mixing step of charging the ethylene-vinyl alcohol copolymer into a mixer or the like and mixing it, and a discharging step of discharging the mixture from the mixer or the like. The present disclosure also relates to a method for producing the above-mentioned processing aid, which includes the mixing step and the discharging step.

[0192] The method of the mixing step is not particularly limited, and may be mixing with or without shear force (kneading). Among these, in order to effectively exhibit the molding processability, kneading is preferred, and melt-kneading is more preferred. When melt-kneading is carried out, the components may be melted in the mixing step or before the mixing step.

[0193] In the above-described manufacturing method, after the discharging step, a molding step of molding the discharged material using a molding machine or the like may be carried out. The method for the molding step is not particularly limited, and examples thereof include extrusion molding, injection molding, blow molding, etc., but among these, extrusion molding is preferred in order to effectively exhibit the molding processability.

[0194] An extruder is used for the extrusion molding. Examples of the extruder include a single-screw extruder, a twin-screw extruder, and a tandem extruder. The extruder typically includes a cylinder, a screw housed in the cylinder, a die attached to the tip of the cylinder, and a hopper for supplying pellets to the cylinder.

[0195] The various conditions for the molding are not particularly limited and can be appropriately set depending on the composition and amount of the composition, the shape and size of the desired molded product, and the like.

[0196] When the processing aid of the present disclosure is a masterbatch, for example, it may be obtained by preparing the processing aid of the present disclosure in advance, adding it to a mixer or the like and the thermoplastic resin (A) and carrying out a mixing step of mixing, and discharging the mixture from the mixer or the like, or it may be obtained by adding the thermoplastic resin (A) and the ethylene-vinyl alcohol copolymer to a mixer or the like and mixing, and discharging the mixture from the mixer or the like.

[0197] In the manufacturing method when the processing aid of the present disclosure is a masterbatch, after the discharging step, a molding step may be carried out in which the discharged product is molded using a molding machine or the like.

[0198] When the processing aid of the present disclosure is a masterbatch, the mixing step, discharging step, and molding step in the production method are the same as those described in the production method of the processing aid of the present disclosure.

[0199] The shape of the processing aid of the present disclosure is not particularly limited and may be powder, granules, pellets, etc., but pellets are preferred because they are easy to handle and mold.

[0200] The processing aids of the present disclosure are particularly useful as processing aids for thermoplastic resins, particularly polyolefins.

[0201] <Thermoplastic resin composition> The thermoplastic resin composition of the present disclosure contains the processing aid of the present disclosure and a thermoplastic resin (B), thereby achieving good processability.

[0202] As the thermoplastic resin (B), the same ones as the thermoplastic resin (A) can be used, and the preferred forms are also the same.

[0203] When the processing aid of the present disclosure is a masterbatch, the thermoplastic resin (A) and the thermoplastic resin (B) may be the same type or different types.

[0204] In the thermoplastic resin composition of the present disclosure, the content of the ethylene-vinyl alcohol copolymer is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, even more preferably 0.04% by mass or more, even more preferably 0.15% by mass or more, particularly preferably 0.2% by mass or more, and is preferably 2% by mass or less, more preferably 1.5% by mass or less, even more preferably 0.8% by mass or less, even more preferably 0.2% by mass or less. The content of the ethylene-vinyl alcohol copolymer may be 0.05% by mass or more, 0.06% by mass or more, or 0.10% by mass or more.

[0205] The thermoplastic resin composition of the present disclosure may contain components other than the processing aid and the thermoplastic resin (B). Examples of components other than the processing aid and the thermoplastic resin (B) that can be used include anti-adhesion agents; ultraviolet absorbers; flame retardants; reinforcing materials such as glass fiber and glass powder; stabilizers such as minerals and flakes; lubricants such as silicone oil and molybdenum disulfide; pigments such as titanium dioxide and red iron oxide; conductive agents such as carbon black; impact resistance improvers such as rubber; hindered phenolic and phosphorus-based antioxidants; nucleating agents such as metal salts and sorbitol acetals; anti-blocking agents; and the above-mentioned lubricant (A).

[0206] The thermoplastic resin composition of the present disclosure may be obtained, for example, by carrying out a mixing step in which the processing aid of the present disclosure is prepared in advance and then charged into a mixer or the like with the thermoplastic resin (B) and a mixing step in which the mixture is discharged from the mixer or the like, or by carrying out a mixing step in which the thermoplastic resin (B), the ethylene-vinyl alcohol copolymer, and, if necessary, the thermoplastic resin (A) are charged into a mixer or the like and then mixed, and a discharging step in which the mixture is discharged from the mixer or the like. The present disclosure also relates to a method for producing the above-mentioned thermoplastic resin composition, which includes the mixing step and the discharging step.

[0207] In the method for producing a thermoplastic resin composition of the present disclosure, after the discharging step, a molding step may be carried out in which the discharged material is molded using a molding machine or the like.

[0208] The mixing step, discharging step, and molding step in the method for producing a thermoplastic resin composition of the present disclosure are the same as those described in the method for producing a processing aid of the present disclosure.

[0209] The thermoplastic resin composition of the present disclosure is preferably produced by a production method including a step of mixing the processing aid of the present disclosure, which contains an ethylene-vinyl alcohol copolymer and has a water content of 0.3 mass% or less, with a thermoplastic resin (B). The present disclosure also relates to the production method.

[0210] In the above-described manufacturing method, the processing aid of the present disclosure may be one whose moisture content has been reduced to 0.3% by mass or less immediately before use. In this case, the moisture reduction method is not particularly limited, but examples thereof include heating at 70°C for 6 hours, with the upper limit of the temperature being not particularly limited, but may be 130°C, and the upper limit of the time being not particularly limited, but may be 48 hours.

[0211] In the above-described manufacturing method, the processing aid of the present disclosure may be one whose moisture content has been reduced to 0.3% by mass or less and then stored in a state where the moisture content is maintained at 0.3% by mass or less. The present disclosure also relates to a method for storing the processing aid of the present disclosure in a state where the moisture content is maintained at 0.3% by mass or less. In this case, the storage method is not particularly limited, but examples include storing the processing aid in a laminated bag or in a device that can maintain a constant humidity, such as a thermo-hygrostat.

[0212] <Molded body> The molded article of the present disclosure uses the thermoplastic resin composition of the present disclosure, and may be obtained, for example, by performing a molding step of molding the thermoplastic resin composition of the present disclosure. The present disclosure also provides a method for producing the molded article of the present disclosure, which includes a molding step. The thermoplastic resin composition of the present disclosure is suitable for molding into a tube-shaped, film-shaped, or sheet-shaped article, but can also be applied to moldings of other shapes.

[0213] The molding step is the same as that described in the method for producing the processing aid of the present disclosure.

[0214] In the molding step, the molding temperature (extrusion temperature) is generally set to a temperature equal to or higher than the melting point of the thermoplastic resin (B) and lower than the decomposition temperature of the ethylene-vinyl alcohol copolymer. When components other than the ethylene-vinyl alcohol copolymer are contained, it is preferable to set the molding temperature taking these components into consideration. In order to ensure that the effects of the processing aid are significantly exhibited, the temperature is preferably in the range of 160°C or higher and 270°C or lower. In the case of extrusion molding, the molding temperature may be referred to as the extrusion temperature.

[0215] Applications of the molded article of the present disclosure are not particularly limited, but examples include bags, covering materials, tableware such as beverage containers, electric wires, cables, pipes, fibers, bottles, gasoline tanks, and various other industrial molded articles.

[0216] <Film> The film of the present disclosure uses the thermoplastic resin composition of the present disclosure, and may be obtained, for example, by carrying out a molding step of molding the thermoplastic resin composition of the present disclosure. The present disclosure also provides a method for producing the molded article of the present disclosure, which includes a molding step. The thermoplastic resin composition of the present disclosure is suitable for molding into a tube-shaped, film-shaped, or sheet-shaped article, but can also be applied to moldings of other shapes.

[0217] The molding step is the same as that described in the method for producing the processing aid of the present disclosure.

[0218] In the molding step, the molding temperature (extrusion temperature) is generally set to a temperature equal to or higher than the melting point of the thermoplastic resin (B) and lower than the decomposition temperature of the ethylene-vinyl alcohol copolymer. When components other than the ethylene-vinyl alcohol copolymer are contained, it is preferable to set the molding temperature taking these components into consideration. In order to ensure that the effects of the processing aid are significantly exhibited, the temperature is preferably in the range of 160°C or higher and 270°C or lower. In the case of extrusion molding, the molding temperature may be referred to as the extrusion temperature.

[0219] Applications of the film of the present disclosure are not particularly limited, but examples include bags, covering materials, tableware such as beverage containers, electric wires, cables, pipes, fibers, bottles, gasoline tanks, and various other industrial molded products.

[0220] Although the embodiments have been described above, it will be understood that various changes in form and details can be made without departing from the spirit and scope of the claims. [Example]

[0221] Next, the present disclosure will be described with reference to examples, but the present disclosure is not limited to these examples.

[0222] In the examples and comparative examples, the following materials were used. (additives) EVOH-1: Ethylene-vinyl alcohol copolymer (ethylene content: 32 mol%, MFR: 1.5 g / 10 min) EVOH-2: Ethylene-vinyl alcohol copolymer (ethylene content: 38 mol%, MFR: 1.6 g / 10 min) EVOH-3: Ethylene-vinyl alcohol copolymer (ethylene content: 44 mol%, MFR: 1.7 g / 10 min) EVOH-4: Ethylene-vinyl alcohol copolymer (ethylene content: 48 mol%, MFR: 6.0 g / 10 min) EVOH-5: Ethylene-vinyl alcohol copolymer (ethylene content: 38 mol%, MFR: 50 g / 10 min) (Thermoplastic resin (A) (carrier resin), thermoplastic resin (B) (matrix resin)) LDPE: Low-density polyethylene (MFR: 3.0 g / 10 min, melting point: 113°C, d = 0.924 g / cm 3 , MIR=29.1) LLDPE-1: Metallocene-catalyzed linear low-density polyethylene (MFR: 0.7 g / 10 min, melting point: 123 °C, d = 0.926 g / cm 3 , MIR=28.1) LLDPE-2: Metallocene-catalyzed linear low-density polyethylene (MFR: 2.0 g / 10 min, melting point: 121 °C, d = 0.925 g / cm 3 , MIR=23.6) LLDPE-3: Ziegler-Natta catalyst-type linear low-density polyethylene (MFR: 0.8 g / 10 min, melting point: 123 °C, d = 0.925 g / cm3 , MIR=27.0) LLDPE-4: Ziegler-Natta catalyst-type linear low-density polyethylene (MFR: 2.0 g / 10 min, melting point: 121°C, d = 0.918 g / cm 3 , MIR=23.2) (Lubricant (A)) Polysorbate 60: Polysorbate 60 Zn-St: Zinc stearate (zinc stearate) Mg-C18(OH): Magnesium 12-hydroxystearate PE-wax#1: General polymerization type polyethylene wax (acid value: 0 mgKOH / g, melting point: 122°C, melt viscosity (140°C): 80 mPa·s) PE-wax#2: Metallocene-catalyzed polyethylene wax (acid value: 0 mgKOH / g, melting point: 100°C, melt viscosity (140°C): 300 mPa·s) PE-wax#3: Acid-modified polyethylene wax (acid value: 17 mg KOH / g, melting point: 107°C, melt viscosity (140°C): 300 mPa·s) PE-wax#4: Oxidized type (high acid value) polyethylene wax (acid value: 30 mg KOH / g, melting point: 102°C, melt viscosity (140°C): 265 mPa·s) (Synergist) PCL: Polycaprolactone (Mw: 80,000, melting point: 55°C) PEG: polyethylene glycol (Mn: 8,000, melting point: 63°C) PEO: Polyethylene oxide (Mv: 150,000-400,000, melting point: 64°C) MB50-002: Silicone (Ultra-high molecular weight silicone-containing masterbatch, manufactured by Dupont) GENIOPLAST PELLET S: Silicone (ultra-high molecular weight silicone, manufactured by Asahi Kasei Wacker) Pebax MV1072: Polyamide-polyether block copolymer (Arkema)

[0223] MFR: The MFR (g / 10 min) of the additives, matrix resin, and carrier resin was measured in accordance with ASTM D 1238 under conditions of 190° C. and a load of 2.16 kgf.

[0224] MIR: The MIR of the matrix resin and carrier resin was determined by HLMI / MI. HLMI: Compliant with ASTM D 1238, MFR (g / 10min) at 190°C and a load of 21.6 kgf MI: Compliant with ASTM D 1238, MFR (g / 10min) at 190°C and a load of 2.16 kgf

[0225] Melting point: The melting points of the additives, matrix resin, and carrier resin were determined using a DSC device (Seiko Corporation) at a rate of 10°C / min, and the melting points were determined as the temperatures corresponding to the maximum values ​​on the heat of fusion curves.

[0226] Moisture content: The mass was measured before and after heating and calculated according to the following formula: The sample was taken three times, and after calculation for each, the average was calculated and used. Moisture content (mass%) = [(mass of processing aid before heating (g)) - (mass of processing aid after heating (g))] / (mass of processing aid before heating (g)) × 100

[0227] Examples A1 to A3, Comparative Examples A1 to A3, Examples B1 to B5, Comparative Example B1, Example C5, Comparative Example C1 First, the additives (pellets) were dried by heating under the conditions below to obtain the moisture contents shown in Tables 1 to 3 (except for Comparative Examples A1, B1, and C1). Then, each material was dry-blended with a matrix resin (LLDPE-1) in the proportions shown in Tables 1 to 3 to obtain thermoplastic resin compositions. The processability of the obtained thermoplastic resin compositions was evaluated by the extrusion evaluation described below. The results are shown in Tables 1 to 3. Heating conditions Example A1: 130°C, 48 hours Example A2: 130°C, 24 hours Examples A3, B1 to B5, and C5: 130°C, 12 hours Comparative example A2: 60℃, 12 hours Comparative Example A3: 45°C, 12 hours

[0228] Examples C1 to C4, Comparative Example C2 First, the carrier resin and additives (pellets) were melt-kneaded in the proportions shown in Table 3 using a twin-screw extruder (TEXαIII manufactured by The Japan Steel Works, Ltd.) under conditions of a cylinder temperature of 180 to 200°C, a die temperature of 200°C, and a screw rotation speed of 400 rpm to obtain masterbatches (MB). The obtained masterbatches were then dried by heating under the conditions described below to obtain the moisture contents shown in Table 3. These were then dry-blended with a matrix resin (LLDPE-1) in the proportions shown in Table 3 to obtain thermoplastic resin compositions. The processability of the obtained thermoplastic resin compositions was evaluated by the extrusion evaluation described below. The results are shown in Table 3. Heating conditions Examples C1 to C4: 130°C, 24 hours Comparative Example C2: 45°C, 6 hours

[0229] In addition, the following contents are the same in Tables 1 to 3. Examples A2 and B1 Examples A3 and C5 Comparative examples A1, B1, C1

[0230] <Extrusion evaluation> Each material was extruded for 60 minutes using a single-screw extruder (HAAKE, Rheomex OS, L / D: 33, screw diameter: 20 mm, die diameter: 2 mm) under conditions of a cylinder temperature of 170-200°C, a die temperature of 200°C, and a shear rate of 450 / s, and evaluated for the following items. Before each test run, linear low-density polyethylene containing 15% silica by mass was added to the hopper, the screw speed was increased to 150 rpm, and purging was performed for approximately 15 minutes. Next, the same LLDPE-1 used in the test was added and purging was performed for approximately 15 minutes. After that, the screw speed was returned to 30 rpm and extrusion was continued until the temperature stabilized. After confirming that the initial pressure had returned, the next experiment was performed. If the initial pressure had not returned, the above purging procedure was repeated until the initial pressure returned, and the next experiment was performed. (Melt fracture (MF) state) Extrusion was performed using only the matrix resin until the pressure stabilized with melt fracture occurring across the entire surface, and the point at which the screw became visible was recorded as time zero. Extrusion continued for 60 minutes. In cases where processing aids were used, these were added to the hopper at time zero. The appearance of the strands at the beginning of extrusion and at the end of extrusion was then visually and tactilely confirmed, and the change in MF observed at the beginning of extrusion was evaluated according to the following criteria. The smaller the value, the better the result. 1: MF completely disappears 2: MF decreases but does not disappear completely 3: MF is the same as when only the matrix resin is used, or there is almost no decrease. (Melt fracture (MF) disappearance time) The time from the zero point described above for the MF condition until the MF disappeared was measured. The shorter the time, the better. If the MF did not disappear after 60 minutes of extrusion, it was marked with "-". (pressure stability) The extrusion pressure was measured for 50 to 60 minutes after the start of extrusion, and the standard deviation was calculated. The closer the value is to 0, the better the result. (Die Build Up (DBU)) The condition of the die after extrusion was visually inspected, and the presence or absence of DBU (eye discharge) was evaluated on a scale of 1 to 5. The smaller the value, the less DBU was generated, and the better the result, with 1 indicating no DBU was generated.

[0231] [Table 1]

[0232] [Table 2]

[0233] [Table 3]

[0234] Examples 1 to 42, Comparative Examples 1 to 4 First, the carrier resin, the ethylene-vinyl alcohol copolymer, the lubricant (A), and the synergist were melt-kneaded in the proportions shown in Tables 4 and 5 using a twin-screw extruder (TEX25αIII manufactured by The Japan Steel Works, Ltd.) at a cylinder temperature of 180 to 200°C, a die temperature of 200°C, and a screw rotation speed of 400 rpm to obtain a masterbatch (MB). The resulting masterbatch was then dried by heating under the conditions shown below to obtain the moisture contents shown in Tables 4 and 5. The resulting masterbatch was then dry-blended with a matrix resin in the proportions shown in Tables 4 and 5 to obtain a thermoplastic resin composition. The processability of the resulting thermoplastic resin composition was evaluated by the extrusion evaluation described below. The results are shown in Tables 4 and 5. Since the ethylene-vinyl alcohol copolymer, lubricant (A), and synergist used were all fluorine-free, the fluorine content of the processing aid was 0% by mass. Heating conditions Examples 1 to 42 and Comparative Examples 1 to 4: 80°C, 12 hours

[0235] <Extrusion evaluation> Each material was extruded for 60 minutes using a single-screw extruder (HAAKE, Rheomex OS, L / D: 33, screw diameter: 20 mm, die diameter: 2 mm) under conditions of a cylinder temperature of 170-200°C, a die temperature of 200°C, and a shear rate of 450 / s, and evaluated for the following items. Before each test run, linear low-density polyethylene containing 15% silica by mass was added to the hopper, the screw speed was increased to 150 rpm, and purging was performed for approximately 15 minutes. Next, the same matrix resin as used in the test was added and purging was performed for approximately 15 minutes. After that, the screw speed was returned to 30 rpm and extrusion was continued until the temperature stabilized. After confirming that the initial pressure had returned, the next experiment was performed. If the initial pressure had not returned, the above purging procedure was repeated until the initial pressure returned, and the next experiment was performed. (Melt fracture (MF) state) Extrusion was performed using only the matrix resin until the pressure stabilized with melt fracture occurring across the entire surface, and the point at which the screw became visible was recorded as time zero. Extrusion continued for 60 minutes. In cases where a processing aid or masterbatch was used, these were added to the hopper at time zero. The appearance of the strands at the beginning of extrusion and at the end of extrusion was then visually and tactilely confirmed, and the change in MF observed at the beginning of extrusion was evaluated according to the following criteria. The smaller the value, the better the result. Disappearance: MF completely disappears Not disappeared: MF remains the same as when only the matrix resin is used, or MF decreases but does not disappear completely. (Die Build Up (DBU)) For samples in which MF had completely disappeared, extrusion evaluation was carried out using long-run molding (3 hours), and the state of the die after extrusion was visually inspected to evaluate the presence or absence of DBU (eye discharge). The evaluation was made on a 5-point scale from 1 to 5. The smaller the value, the less DBU was generated and the better the result, with 1 indicating that no DBU was generated.

[0236] <Masterbatch MFR> For Examples 43 to 45, the carrier resin and additives were melt-kneaded in the proportions shown in Table 6 using a twin-screw extruder (TEX25αIII manufactured by The Japan Steel Works, Ltd.) at a cylinder temperature of 180 to 200°C, a die temperature of 200°C, and a screw rotation speed of 400 rpm to obtain a masterbatch (MB) with an additive concentration of 25% by mass. The MFR (g / 10 min) of the resulting masterbatch was measured (in accordance with ASTM D 1238, at 190°C and a load of 2.16 kgf).

[0237] [Table 4]

[0238] [Table 5]

[0239] [Table 6]

Claims

1. Contains an ethylene-vinyl alcohol copolymer, The moisture content is 0.3% by mass or less, A processing aid for extrusion molding, which is a masterbatch further comprising a thermoplastic resin (A).

2. 2. The extrusion molding processing aid according to claim 1, wherein the ethylene-vinyl alcohol copolymer has a melt flow rate of 50 g / 10 min or less at 190° C. and a load of 2.16 kgf.

3. 3. The extrusion molding processing aid according to claim 1, wherein the ethylene-vinyl alcohol copolymer has an ethylene content of 5 to 50 mol %.

4. The ethylene-vinyl alcohol copolymer has a melt flow rate of 1.5 g / 10 min or more and 50 g / 10 min or less at 190° C. and a load of 2.16 kgf, 3. The extrusion molding processing aid according to claim 1, wherein the ethylene-vinyl alcohol copolymer has an ethylene content of 32 to 48 mol %.

5. 3. The extrusion molding processing aid according to claim 1, wherein the thermoplastic resin (A) is a polyolefin resin.

6. 6. The extrusion molding processing aid according to claim 5, wherein the polyolefin resin is polyethylene.

7. The extrusion molding processing aid according to claim 1 or 2, wherein the mass ratio of the thermoplastic resin (A) to the ethylene-vinyl alcohol copolymer (thermoplastic resin (A):ethylene-vinyl alcohol copolymer) is 99:1 to 40:

60.

8. The thermoplastic resin (A) is at least one selected from the group consisting of low-density polyethylene, metallocene-catalyzed linear low-density polyethylene, and Ziegler-Natta-catalyzed linear low-density polyethylene, The extrusion molding processing aid according to claim 1 or 2, wherein the mass ratio of the thermoplastic resin (A) to the ethylene-vinyl alcohol copolymer (thermoplastic resin (A):ethylene-vinyl alcohol copolymer) is 93:7 to 25:

75.

9. 3. The extrusion molding processing aid according to claim 1 or 2, which is substantially free of fluorine.

10. 3. The extrusion molding processing aid according to claim 1, which has a melt flow rate of 0.01 to 100 g / 10 min at 190° C. and a load of 2.16 kgf.

11. A thermoplastic resin composition comprising the extrusion molding processing aid according to claim 1 and a thermoplastic resin (B).

12. An extrusion molding processing aid comprising an ethylene-vinyl alcohol copolymer and having a moisture content of 0.3 mass% or less, and a thermoplastic resin (B), The thermoplastic resin composition has an ethylene-vinyl alcohol copolymer content of 0.001 to 2 mass %.

13. The thermoplastic resin composition according to claim 11 or 12, wherein the thermoplastic resin (B) is a polyolefin resin.

14. The thermoplastic resin composition according to claim 13, wherein the polyolefin resin is polyethylene.

15. The thermoplastic resin composition according to claim 11, wherein the content of the ethylene-vinyl alcohol copolymer is 0.001 to 2% by mass.

16. The thermoplastic resin (B) is at least one selected from the group consisting of metallocene catalyst type linear low density polyethylene and Ziegler-Natta catalyst type linear low density polyethylene, The thermoplastic resin composition according to claim 11 or 12, wherein the content of the ethylene-vinyl alcohol copolymer is 0.04 to 0.2 mass %.

17. The thermoplastic resin composition according to claim 12, wherein the ethylene-vinyl alcohol copolymer has a melt flow rate of 50 g / 10 min or less at 190° C. and a load of 2.16 kgf.

18. The thermoplastic resin composition according to claim 12 or 17, wherein the ethylene-vinyl alcohol copolymer has an ethylene content of 5 to 50 mol %.

19. The ethylene-vinyl alcohol copolymer has a melt flow rate of 1.5 g / 10 min or more and 50 g / 10 min or less at 190° C. and a load of 2.16 kgf, The thermoplastic resin composition according to claim 12 or 17, wherein the ethylene-vinyl alcohol copolymer has an ethylene content of 32 to 48 mol %.

20. The thermoplastic resin composition according to claim 12 or 17, wherein the extrusion molding processing aid is a masterbatch further containing a thermoplastic resin (A).

21. The thermoplastic resin composition according to claim 20, wherein the thermoplastic resin (A) is a polyolefin resin.

22. The thermoplastic resin composition of claim 21, wherein the polyolefin resin is polyethylene.

23. The thermoplastic resin composition according to claim 20, wherein the mass ratio of the thermoplastic resin (A) and the ethylene-vinyl alcohol copolymer (thermoplastic resin (A):ethylene-vinyl alcohol copolymer) is 99:1 to 40:

60.

24. The thermoplastic resin (A) is at least one selected from the group consisting of low-density polyethylene, metallocene-catalyzed linear low-density polyethylene, and Ziegler-Natta-catalyzed linear low-density polyethylene; The thermoplastic resin composition according to claim 20, wherein the mass ratio of the thermoplastic resin (A) to the ethylene-vinyl alcohol copolymer (thermoplastic resin (A): ethylene-vinyl alcohol copolymer) is 93:7 to 25:

75.

25. The thermoplastic resin composition according to claim 12 or 17, wherein the extrusion molding processing aid is substantially free of fluorine.

26. The thermoplastic resin composition according to claim 20, wherein the extrusion molding processing aid has a melt flow rate of 0.01 to 100 g / 10 min at 190° C. and a load of 2.16 kgf.

27. A film using the thermoplastic resin composition according to claim 11 or 12.

28. The method for producing the processing aid for extrusion molding according to claim 1 or 2, comprising a mixing step and a discharging step.

29. The method for producing the thermoplastic resin composition according to claim 11 or 12, comprising a mixing step and a discharging step.

30. 28. A method for producing the film of claim 27, comprising a molding step.

Citation Information

Patent Citations

  • Thermoplastic resin composition

    JP1977051440A

  • Composition of linear polyethylene and ethylene / vinyl alcohol polymer and low stickiness film thereof

    JP1989215840A

  • Multilayer stretch film

    JP2007290379A

  • Injection molding

    JP2019214695A

  • Resin composition, manufacturing method therefor, molded body, and multilayer structure

    JP2020090646A